(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2026)
This study looks at how a bidirectional high-gain converter (BDHGC) can support charging electric vehicles (EVs) using a PV array. The solar irradiation varies, and the PV system’s output is increased with an MPPT technique before it is sent to the BDHGC. The converter increases the voltage and allows power to move back and forth for successful charging. Both switching and conduction losses are studied in detail by building MATLAB/Simulink simulations. The system uses a relay feedback control system to keep the output voltage steady whenever the load changes. From the simulation, it is evident that the system gives high efficiency and stable control, which makes voting solar-powered EV charging a possibility.